Blockchain Implementation In Zakat Management: Potentials And Challenges In The Digital Era - Farid Nur Isjayanto; Ade Lia Vebrianti; Misbahul Munir (Prodi Ekonomi Syariah Universitas Pangeran Diponegoro Nganjuk, 2025)
Blockchain technology offers promising opportunities to reform and enhance zakat management by increasing transparency, accountability, and efficiency through immutable distributed ledgers and automated smart contracts that ensure compliance with Islamic principles such as nisab and haul. It facilitates direct, real-time tracking of zakat funds from muzakki to mustahiq, reducing the potential for fraud and administrative inefficiencies. However, despite these benefits, the adoption of blockchain in zakat systems faces significant multidimensional challenges. Technically, issues like scalability, energy consumption, and interoperability hinder seamless integration and widespread use. Regulatory frameworks specific to blockchain application in zakat are largely absent in many countries, creating legal uncertainty and complicating compliance with data protection laws such as GDPR and Indonesia’s UU PDP. Socially and culturally, the limited digital literacy and skepticism toward new technologies among stakeholders slow acceptance and trust in blockchain-based zakat systems. To fully realize blockchain’s potential in transforming zakat management, a comprehensive mitigation approach addressing technical infrastructure, clear and adaptive regulations, and targeted educational programs to improve digital competency and trust is essential. This multi-stakeholder effort, involving regulators, Islamic scholars, technologists, and zakat institutions, is critical to ensure that the benefits of blockchain align not only with operational efficiency but also with Shariah compliance and social acceptance.